A Fundamental Study on Circularly Polarized Double-Loop Antennas with Quasi-Two Sources - Hirose, Kazuhide; Hirose, Mitsuki; Mita, Shintaro; Nakano, Hisamatsu (Applied sciences, 2024)
Two concentric double-loop antennas were analyzed using the moment method to increase the 3 dB axial ratio bandwidth. Each antenna has a driven loop connected to a branched feedline that is vertical to the ground plane. First, a parasitic loop was added outside of the driven one with a spacing of S. It was found that the axial ratio bandwidth has a maximum value of 23% for S = 0.02 wavelengths. Next, we moved a parasitic loop inside of the driven one. It was revealed that the antenna shows an axial ratio bandwidth of 40%, which is three times as wide as that of a single-loop antenna. The analysis results were verified with experimental work.